2008
DOI: 10.1148/rg.282075060
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Facial Fractures: Children Are Not Just Small Adults

Abstract: Radiologic imaging is essential for diagnosing pediatric facial fractures and selecting the optimal therapeutic approach. Trauma-induced maxillofacial injuries in children may affect functioning as well as esthetic appearance, and they must be diagnosed promptly and accurately and managed appropriately to avoid disturbances of future growth and development. However, these fractures may be difficult to detect on images, and they are frequently underreported. The interpretation of facial radiographs is particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
157
2
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(181 citation statements)
references
References 33 publications
8
157
2
7
Order By: Relevance
“…Because of the relative prominence of the skull to face, children younger than 5 years have a much higher chance of sustaining basilar skull fractures with frontal and orbital fractures, whereas children with facial skeletal proportions similar to adults are more likely to sustain midface and mandibular fractures. 3,4 Children younger than 2 years tend to have flexible bones, making greenstick fractures more common. After the age of 2 to 3 years, increased bone mineralization makes greenstick fractures less common.…”
Section: Pediatric Growth Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the relative prominence of the skull to face, children younger than 5 years have a much higher chance of sustaining basilar skull fractures with frontal and orbital fractures, whereas children with facial skeletal proportions similar to adults are more likely to sustain midface and mandibular fractures. 3,4 Children younger than 2 years tend to have flexible bones, making greenstick fractures more common. After the age of 2 to 3 years, increased bone mineralization makes greenstick fractures less common.…”
Section: Pediatric Growth Considerationsmentioning
confidence: 99%
“…There is a high correlation between facial fractures and intracranial trauma in the pediatric population; studies have demonstrated that any suspicion of facial trauma warrants computed tomographic (CT) scan evaluation in the pediatric population. 3,15,16 Interestingly, initial Glasgow coma scale score and loss of consciousness during the accident are poor predictors of intracranial trauma in pediatric patients (though these are commonly used indicators in adults). The mechanism of injury is the most reliable predictor of intracranial trauma in pediatric patients.…”
Section: Diagnosismentioning
confidence: 99%
“…Facial growth, paranasal sinus development, dentition and bone structure all affect the pattern of facial structures in children. 3 A green stick fracture is a fracture in which one cortex of the bone is broken and the other cortex is bend. Green stick fracture commonly occur in children due to thin cortices, inherent elasticity of bone, thick surrounding layer of adipose tissue and the relatively larger amount of medullary bone held by a strong periosteal support results in a high incidence of greenstick fractures in children.…”
Section: Discussionmentioning
confidence: 99%
“…Facial growth, paranasal sinus development, dentition, and bone structure all affect the pattern of facial fractures in children. 5 Management of children with primary or mixed dentition is complicated by several factors. First is the presence of secondary, unerupted teeth in the mandible body until 6 years of age or longer.…”
Section: Discussionmentioning
confidence: 99%